Pengembangan Bahan Ajar Pada MateriKerusakan Lingkungan Mata Pelajaran IPSSMP Kelas VIII - Faradika, Megan; , Bapak Drs. Suharjo, M.S (2016)
A minimum of knowledge that fined by students in class VIII Junior High School from their hand book, appear idea reseacher to developing teaching materials. This research is aims to developing teaching materials in order to be usefull for student then that teaching material experimented with Pre-Experimental Design with kinds One-Group Pretest-Posttest in Junior High School 2 Colomadu Karanganyar in class VIII C samples as many as 33 students using numbered head together strategy to see wether this taching material exist is increasing of student learning result. The technique of data analysis is used is paired sample t test with tabulation value of pretest is 66,21% and increase to 79,39%. So it is showing that teaching material developing by researcher with title "Kerusakan Lingkungan Hidup Di Sekitar Kita" is effective used with diverification learning result as much as 13,18%.